Copious watery nipple discharge caused by a discontinuous ventriculoperitoneal shunt. Issue 5 (19th November 2019) - Ambinder, Emily B.; Eisner, David
Abstract: Breast‐related complications of ventriculoperitoneal (VP) shunts are rare. We present a case of a woman with a VP shunt with copious watery nipple discharge following a fall. Shunt discontinuity was identified on a diagnostic mammogram, and the nipple discharge was confirmed to be cerebrospinal fluid (CSF). Symptoms resolved with shunt revision.